Study on core essential elements for O2O business model with value net theory. (14th June 2019) - Wan, Jiang Ping; Zhu, Ya Hui; Jiang, Qiao Wen
The O2O business model concept was given based on literature review. The O2O business model framework was established and the most basic seven major elements were identified in our research with value net theory as follow: customer, telecom operator, content provider, service provider, software provider, third-party payment platform and offline business entity. Then, we identified eight secondary elements and 22 three-level elements of O2O business model with Delphi, and the O2O business model core essential elements evaluation model was also established. We analysed the model systematically and figured out top ten core elements with analytic network process as follow: network speed and stability, mining the customer subject requirements, insight to customer demand, control the trading risk, the core technology research and development, the life service payment platform, after payment platform, financial services platform development, outburst requirements fulfilment and maintenance of direct correlation among enterprises. The top ten elements mainly concentrated in four dimensions as follow: customer, telecom operators, third-party payment platform, and software providers. We hope that the research can provide enlightenment to O2O business model essence and insight to O2O future trends.